The Impact of Perceived Value, Satisfaction and Culture on Gojek Customer Loyalty in Yogyakarta - Putri Sundariningsih (MANAJEMEN DEWANTARA, 2021)
The Covid-19 pandemic which hit across the world have brought essential changes in the marketing area, such as the one concerning customer loyalty especially in an online transportation service (Gojek) in Yogyakarta, Indonesia. Customer loyalty faced the problem of restrictions on access and activities related to transportation. Yet, practically the business process must keep going in any situation. This research investigates the factors that affect customer loyalty which are perceived value, satisfaction, and culture. Previous studies demonstrate that perceived value and satisfaction influences customer loyalty. This research subsequently investigates another factor of customer loyalty, i.e. culture. This research is a combination between those conducted by Diallo, Diop-Sall, Djelassi, and Godefroit-Winkel (2018) and Parida and Sahney (2017). The relationship between perceived value and satisfaction toward customer loyalty adopted from Diallo, Diop-Sall, Djelassi, and Godefroit-Winkel (2018), hereinafter the additional variable namely culture that affect customer loyalty adopted from Parida and Sahney (2017). This research collected data from 100 respondents and tested the hypotheses by using partial least square (PLS). The results showed that the customer loyalty of Gojek in Yogyakarta is still significant based on perceived value, satisfaction, and culture factors. Specifically, the culture variables developed in this study have a significant effect on customer loyalty. This research provides an insight that Gojek customer loyalty in Yogyakarta remains significant even though it is hit by Covid-19 pandemic based on perceived value, satisfaction, and culture factors. It implies that the management of Gojek should increase the customer loyalty during Covid-19 pandemic. In addition, the results of this study give an insight to academics in studying and developing research in the marketing field, especially under the topic of customer loyalty.Â Keywords: customer loyalty, perceived value, satisfaction, culture.